THE INFLUENCE OF CREATIVE ECONOMY, BANK CREDIT, AND COMMUNITY SAVINGS ON ECONOMIC GROWTH, POVERTY, AND UNEMPLOYMENT: EVIDENCE FROM INDONESIAN PROVINCES (2015-2024) - Ikhda Rofiqotul Khoiriyah; Feri Dwi Riyanto (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of the creative economy, bank credit, and community savings on economic growth, poverty, and unemployment in Indonesia during the period 2015–2024. The research adopts a quantitative approach using panel data from 34 provinces, sourced from Badan Pusat Statistik and Bank Indonesia. The analytical method employed is panel data regression, with the Fixed Effect Model selected as the best-fitting model based on the Chow Test and Hausman Test results. The findings indicate that the creative economy does not have a significant effect on economic growth and poverty; however, it has a positive and significant effect on unemployment. Bank credit demonstrates a positive and significant influence on economic growth, while exerting a negative and significant effect on poverty and unemployment, suggesting its important role in promoting inclusive development. Meanwhile, community savings positively affect economic growth but are also associated with increases in poverty and unemployment, indicating that savings accumulation alone does not automatically translate into productive economic expansion.Simultaneously, the three independent variables significantly influence economic growth, poverty, and unemployment. These results highlight the critical importance of optimizing financial intermediation, strengthening the productive allocation of savings, and enhancing inclusive economic development policies to achieve balanced and sustainable economic outcomes across provinces in Indonesia. Keywords: Creative Economy; Bank Credit; Community Savings ; Economic Growth